Diesel exhaust particles induced oxidative stress, autophagy, and apoptosis in human umbilical vein endothelial cells - Yang Guo; Longfei Guan; Yu Ji; Hangil Lee; Wenjing Wei; Changya Peng; Xiaokun Geng; Yuchuan Ding (Wolters Kluwer Medknow Publications, 2020)
Background: Air pollution is one of the greatest public health concerns worldwide. In order to understand its mechanism of harm, we investigated the effects of diesel exhaust particles (DEPs), one of the major constituents of ambient air pollutants, on reactive cell viability, oxygen stress, autophagy, and apoptosis. Materials and Methods: In in vitro human umbilical vein endothelial cell (HUVEC) model, cells were exposed to freshly dispersed DEP preparations at 0, 12.5, 25, 50, 100, or 200 µg/mL for 24 h or at 50 µg/mL DEP for 1, 3, 6, 12, or 24 h. Cell survival and oxidative stress were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX), and generation of reactive oxygen species (ROS). Protein expressions of autophagy (Beclin-1, p62, and light chain 3 [LC3]-II) and apoptosis (Bcl2 and Bax) were assayed by Western blotting. Results: DEP induced a significant dose-dependent and temporal decrease in cell viability and increase in ROS generation and NOX activity, in association with decreased or increased protein levels of p62 or Beclin-1, as well as conversion of the LC3 in a dose-dependent manner. DEP increased pro-apoptotic protein Bax and decreased anti-apoptotic protein Bcl2. Conclusions: These results demonstrated that DEP exposure induced cytotoxicity, oxidative stress, autophagy, and apoptosis in HUVECs. Novel insight into the mechanisms of cardiovascular diseases caused by air pollution may be provided through these findings.